2007
DOI: 10.1111/j.1744-7917.2007.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent development of diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae) on two brassicaceous host plants

Abstract: The effect of temperature on the development of the Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), was evaluated at eight constant temperatures (10, 15, 20, 25, 28, 30, 32.5 and 35°C), with relative humidity of 65% and a photoperiod of 14:10 (L:D) hours on two host plants, cauliflower, Brassica oleracea var. botrytis and cabbage, Brassica oleracea var. capitata. The low temperature threshold was estimated to be 7.06°C and 7.84°C and the thermal constant was 263.74 and 261.58 degree‐days for P. xylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 27 publications
9
76
6
1
Order By: Relevance
“…The observed declines in emergence rates at the lowest and highest temperatures in this study are consistent with the observations of Li et al (2013). Similar results were observed in Plutella xylostella by Golizadeh et al (2007) who studied its temperature-dependent development on cabbage, and also found that pupal development times decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 91%
“…The observed declines in emergence rates at the lowest and highest temperatures in this study are consistent with the observations of Li et al (2013). Similar results were observed in Plutella xylostella by Golizadeh et al (2007) who studied its temperature-dependent development on cabbage, and also found that pupal development times decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 91%
“…In this discussion, it is certain that the amount and quality of available food exert a direct influence on host preference and affect the rate of growth, development time, body weight, and survival of lepidopterans, including S. frugiperda (Nation, 2002;Golizadeh et al, 2009). Therefore, in order to analyze the factors that affect the development of insects, it is necessary to know the parameters that help establish nutritional comparisons between different hosts (Scriber and Slansky, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…3) is a highly mobile insect, and is considered as the most damaging insect pest of Brassica crops worldwide. With an estimated control cost of nearly US$ 1 billion annually (Talekar and Shelton, 1993;Pivnick et al, 1994;Sarfraz et al, 2006;Golizadeh et al, 2007;Shelton et al, 2008), it has been the greatest threat to Brassica production in many regions of the world, with crop loss of 90% in some cases (Verkerk and Wright, 1996;Charleston and Kfir, 2000). The diamondback moth was first noticed as a pest in South Africa in the early 1900s (Charleston and Kfir, 2000).…”
Section: The Diamondback Moth (Plutella Xylostella)mentioning
confidence: 99%